The expectations and acceptability of a smart nursing home model among chinese older adults: a mixed methods study - Zhao, Yuanyuan; Sazlina, Shariff-Ghazali; Rokhani, Fakhrul Zaman; Chinna, Karuthan; Su, Jing; Chew, Boon-How (BMC, 2024)
Background Smart nursing homes (SNHs) integrate advanced technologies, including IoT, digital health, big data, AI, and cloud computing to optimise remote clinical services, monitor abnormal events, enhance decision-making, and support daily activities for older residents, ensuring overall well-being in a safe and cost-effective environment. This study developed and validated a 24-item Expectation and Acceptability of Smart Nursing Homes Questionnaire (EASNH-Q), and examined the levels of expectations and acceptability of SNHs and associated factors among older adults in China.